Dampak Inkubator Bisnis Terhadap Minat Berwirausaha Mahasiswa di Universitas Tridinanti Palembang - Mayasari, Veny; Liliana, Liliana; Seto, Agung Anggoro (Universitas Medan Area, 2019)
This research aims to find out the impact of business incubator activities against the interests of student entrepreneurship at the University of Tridinanti. This type of research is comparative. The population are 5,737 people. Sampling techniques using Accidental sampling by the number of samples was determined as many as 200 respondents. The primary data sources with the techniques of data collection using the questionnaire, interview and observation. Data analysis techniques using paired sample t test. The results showed that there is a difference of interest a student entrepreneurship before and after follow the business incubator activities with significance value of 0.000 where the average value of interest in entrepreneurship student business incubator activities after following increased by 1.960 point than before following the activities of the business incubator. The research also found that business incubator activities have changed the mindset of most college students.